Accelerating EFL Learners’ Speaking and Listening Skills through the Audio-Lingual Teaching Method - Karim, Sayit Abdul; Sudiro, Suryo; Isnanisa, Rizqi; Ningrum, Apriliani Dewi Puspita; Maemunah, Siti (Universitas Muhammadiyah Kalimantan Timur, 2024)
Teaching English as a foreign language is a great challenge for EFL teachers in Indonesia because they are expected to be more creative and innovative in arousing students' attention during the learning-teaching process. The Audio-Lingual Method (ALM) is one of the teaching methods in foreign language learning that may be utilized in teaching speaking and listening skills. This conceptual article attempts to explore how ALM can accelerate EFL learners’ speaking and listening skills. Therefore, it discusses the concept of ALM, the strategy of ALM in learning speaking and listening skills, as well as the benefits of using ALM in learning language skills. A descriptive qualitative research approach with library research design was utilized to review and explore the concept, strategy, and benefits of using the ALM in accelerating EFL students’ speaking and listening skills. This method enables researchers to delve into relevant information and experts' perspectives on the ALM. In addition, it gains more insight into learning and teaching speaking and listening skills, and reviews the learning of speaking and listening skills using the ALM. The data were obtained from previous research findings, related articles, and documentation on the ALM. The data were qualitatively analyzed and comprehensively described the issues and provided valuable insights for all stakeholders in the field of education, including EFL teachers, students, school curriculum developers, and researchers.